The Feasibility of Applying Virtual Reality Simulation to the Coal Mining Operations - Stothard, Phillip (AUSTRALASIAN INST MINING & METALLURGY, LATROBE VALLEY BRANCH, 2003)
In the last two decades, equipment used in the coal mining operations has become much more sophisticated. The way that work is organised and performed in the industry has also changed significantly. Changes in equipment specification or procedures inevitably means that the risk associated with that equipment or procedure also changes. In an attempt to address this the Joint Coal Board Occupational Health and Safety Trust (JCB) commissioned the University of New South Wales Mining Research Centre and Mine Site Technologies to perform a feasibility study into the development and deployment of Virtual Reality (VR) based training simulators in the New South Wales coal industry. The main aims of the study were to identify, the key providers of VR Technology, the VR options available to the JCB and the information that would need to be included in any simulator. It was anticipated that a critical assessment of these components would produce a format for a cost effective, state of the art simulator that could be readily accessed by all mines. The expectations of the feasibility study were that VR should offer three-dimensional (3D) simulations that are interactive, high-resolution models of real environments based on best practice Safety Management Plans. It was anticipated that the simulations would allow trainees to experience the consequences of poor decision-making and allow them to learn from their mistakes in a safe and forgiving environment. It was envisaged that such simulators would become an addition to the existing training methods used in the industry.